Successful endovascular coiling of infectious cerebral aneurysm following Staphylococcus haemolyticus endocarditis. Issue 11 (November 2021) - Matsuzono, Kosuke; Ishiyama, Yusuke; Higaki, Ayuho; Namba, Katsunari; Aoyama, Yutaka; Igarashi, Takeshi; Miura, Kumiko; Ozawa, Tadashi; Mashiko, Takafumi; Koide, Reiji; Tanaka, Ryota; Harada, Kenji; et al.
Recent reports suggest that Staphylococcus haemolyticus can cause infective endocarditis (IE). However, no data are available regarding infectious intracranial aneurysm (IIA) following S. haemolyticus endocarditis. Endovascular coiling is a challenging approach for the treatment of IIA. We describe the case of a 63-year-old woman who suddenly developed aphasia and dysarthria following an acute cerebral infarction in her left insular and temporal cortex. After a total hysterectomy at the age of 39, the patient had suffered from recurrent bacterial pyomyositis in her legs. At admission, there was no evidence of cerebral aneurysm, as assessed by magnetic resonance angiography, and no vegetation, as assessed by transesophageal echocardiography (TEE), resulting in an incorrect diagnosis. However, subarachnoid hemorrhage and development of cerebral aneurysm in the left middle cerebral artery occurred within 1 week of hospitalization. Continuous positive blood culture results and a second TEE finally revealed that IE was caused by S. haemolyticus. Coil embolization of the IIA was successful on day 26 after symptom onset; after this procedure, the patient began to recover. This case demonstrates that S. haemolyticus -induced endocarditis can cause IIA. Endovascular coiling is a potentially effective approach to treat IIA.